Исследование системы каменный уголь-вода-метан при низких температурах - Ульянова, Е.В. (Физико-технические проблемы горного производства, 2005)
Використовування низьких температур при ЯМР-дослідженнях водо-метано-насиченого вугілля дає можливість розділити внески води і метану в загальні ЯМР-спектри і визначити їх кількість. Use of low temperatures at NMR-researches of saturated coals with water-methane is put possibility to divide contributions of water and methane to the general NMR-spectrums and to define their amount.